COVID-19 pandemic and HIV treatment continuity: Factors associated with treatment abandonment in Maputo province, Mozambique (Research, Society and Development, 2026)
Infection with HIV/AIDS remains a major public health challenge, particularly in sub-Saharan Africa. In Mozambique, the high prevalence of the disease requires effective strategies to ensure continuity of antiretroviral therapy. However, the COVID-19 pandemic caused significant disruptions to health systems, affecting access to services and contributing to treatment interruption among many patients. This study aimed to analyse the factors associated with HIV treatment abandonment during the pandemic in Maputo Province and discuss its implications for public health. The methodology consisted of a narrative review of scientific and documentary literature, including national and international reports and scientific articles published over the last ten years. Evidence related to adherence to antiretroviral therapy, determinants of treatment abandonment, and the impact of the pandemic on HIV services was analysed. The results indicate that treatment interruption was associated with multiple factors, including fear of infection in health facilities, mobility restrictions, transportation difficulties, loss of income, and food insecurity. Additionally, structural limitations within the health system, such as long waiting times and reduced community support activities, contributed to treatment discontinuation. The study concludes that the COVID-19 pandemic significantly affected the continuity of HIV treatment in Maputo Province, highlighting the need to strengthen retention strategies and ensure continuity of essential health services during public health emergencies.